Imidacloprid disturbed the gut barrier function and interfered with bile acids metabolism in mice. (November 2020) - Yang, Guiling; Yuan, Xianling; Jin, Cuiyuan; Wang, Dou; Wang, Yanhua; Miao, Wenyu; Jin, Yuanxiang
Abstract: The toxicity of neonicotinoid insecticide imidacloprid (IMI) to mammals has recently received increasing attention. However, the effects of IMI on the gut barrier and liver function of male C57BL/6J mice are still unknown. The study showed that exposure to IMI could reduce relative liver weights, change hepatic tissue morphology and induce hepatic oxidative stress. The gut barrier function was greatly impaired by IMI exposure, which might increase the body's susceptibility to harmful substances in the gut. Meanwhile, the synthesis and metabolism of hepatic bile acids (BAs) was also affected by IMI exposure. The levels of serum and hepatic total bile acids (TBAs) decreased; in contrast, the fecal TBA levels increased after exposure to 30 mg/L IMI for 10 weeks. Sequencing of colonic contents revealed that the operational taxonomic units (OTUs) and α-diversity index increased and that the gram-negative bacteria overgrew, indicating that the balance of the gut microbiota was disrupted. The present study indicated that subchronic exposure to IMI interfered with the gut barrier function, interfering with BAs metabolism and causing gut microbiota imbalance in male C57BL/6J mice. Taken together, IMI residues appear to be potentially toxic to mammals and even humans. Graphical abstract: Image 1 Highlights: Subchronic imidacloprid exposure impaired the function of the gut barrier in male C57BL/6J mice. Subchronic exposure of imidacloprid induced gut microbiota imbalance in mice. Subchronic exposure of imidacloprid interfered with bile acids metabolism. Imidacloprid induced liver injury may be the direct reason for bile acids metabolism. Abstract : The present study reported that subchronic exposure to imidacloprid disturbed with the gut barrier function, interfering with BAs metabolism and causing gut microbiota imbalance in mice.